Growth and Element Uptake by Salt-Sensitive Crops under Combined NaCl and Cd Stresses - Ondrasek, Gabrijel; Rengel, Zed; Maurović, Nada; Kondres, Nada; Filipović, Vilim; Savić, Radovan; Blagojević, Boško; Tanaskovik, Vjekoslav; Gergichevich, Cristian Meriño; Romić, Davor (MDPI AG, 2021)
To test an assumption that organic soil can ameliorate nutritional disorders associated with metal and salinity stresses, we exposed salt-sensitive strawberry and lettuce to four salinity (0-60 mM NaCl) and three contamination (0.3-5 mg Cd/kg) rates in peat (pHH2O = 5.5). The results showed that, even at 20 mM NaCl, salinity stress exerted a dominant effect on rhizosphere biogeochemistry and physiological processes, inducing leaf-edge burns, chlorosis/necrosis, reducing vegetative growth in crops; at ≥40 mM, NaCl mortality was induced in strawberry. Signifiacntly decreased K/Na, Ca/Na and Mg/Na concentration ratios with raising salinity were confirmed in all tissues. The combined CdxNaCl stresses (vs. control) increased leaf Cd accumulation (up to 42-fold in lettuce and 23-fold in strawberry), whereas NaCl salinity increased the accumulation of Zn (>1.5-fold) and Cu (up to 1.2-fold) in leaves. Lettuce accumulated the toxic Cd concentration (up to 12.6 mg/kg) in leaves, suggesting the strong root-to-shoot transport of Cd. In strawberry Cd, concentration was similar (and sub-toxic) in fruits and leaves, 2.28 and 1.86 mg/kg, respectively, suggesting lower Cd root-to-shoot translocation, and similar Cd mobility in the xylem and phloem. Additionally, the accumulation of Cd in strawberry fruits was exacerbated at high NaCl exposure (60 mM) compared with lower NaCl concentrations. Thus, in salinized, slightly acidic and organically rich rhizosphere, pronounced organo- and/or chloro-complexation likely shifted metal biogeochemistry toward increased mobility and phytoavailability (with metal adsorption restricted due to Na+ oversaturation of the caton exchange complex in the substrate), confirming the importance of quality water and soils in avoiding abiotic stresses and producing non-contaminated food.